Study of the effects of heating on the physical, optical, and electrical properties of NiO thin films synthesized using a low-cost sol-gel method - Muhammad Yasir Khan; M. Wasim Akhtar; Muhammad Furqan Ali Khan; Zeeshan Abbass; Fayyaz -ur- Rasheed; Muhammad Saquib Ali; Noman Pirzada; Raja Shahbaz (Mehran University Research Journal of Engineering and Technology, 2024)
Developments in low-cost techniques for growing high-quality nickel oxide thin films (NiOTFs) are critical enablers for the fabrication of NiO-based devices, particularly solar cells, light-emitting diodes, lasers, and many other applications. In this study, it has been demonstrated that the optical, electrical, and structural characteristics of NiOTFs coated on glass substrate employing a low-cost solution method are strongly influenced by post-thermal annealing treatments in ambient air. A comprehensive study was carried out on the characteristics of the deposited NiOTFs. X-ray diffraction (XRD) measurements indicate the enhancement of the crystal quality of films after annealing. There is a noticeable change and improvement in coated NiOTFs with heat treatment at 300 and 600 ℃ due to clear shifts in density. During the heating temperature increment, the energy of the band gap was shifted from 3.63 to 3.44 eV, and the electrical resistance of the NiOTFs varied from 1020 to 700 Ω-cm. Furthermore, the results indicate that the low-cost sol-gel (SG) deposition technique has a greater potential for producing high-quality p-type NiOTFs with minimal defects for electronic device applications.